Einstein's Universe : The Layman's Guide - Calder, Nigel (New York Penguin books, 1979)
In this centenary celebration of Einstein's birth, Calder offers lucid commentary on the landmark works Special Relativity and General Relativity which deal, respectively, with high-speed motion and gravity, revealing the extent to which Einstein revolutionized man's ideas about the universe.
Include Illustrations and Index
Keywords: Relativity (Physics) -- Astrophysics -- Cosmology -- Einstein, Albert, 1879-1955